A glance into traditional pig slaughtering practices in Vietnam and opportunities for zoonotic disease prevention - Ting, N.I.; Sinh Dang-Xuan; Gilbert, Jeffrey; Nguyen Thao Thi Nguyen; Lam, S.; Hung Nguyen-Viet (Frontiers Media, 2023)
Introduction: African swine fever in Vietnam is contributing to existing concerns over zoonotic disease transmission from sick pigs to humans. While slaughterhouses are key sites of occupational hazards to workers and contamination of meat, the specific slaughtering practices contributing to zoonotic occupational and foodborne disease risks remain under-researched. Our objective is to identify and characterize aspects of pig slaughtering processes that contribute to such risks.